Narratives of Revenge and Identity in the Film Munich (2005): Literary and Political Analysis (Universitas Pendidikan Indonesia, 2026)
Steven Spielberg's film Munich (2005) presents a narrative that departs from the tragedy of the 1972 Munich Olympics and Mossad's retaliatory response against the group deemed responsible. The representation of violence in this film has sparked widespread debate in the realm of literary and political criticism, particularly regarding the ethics of revenge, state legitimacy, and the impact of individual and collective trauma. This study aims to analyze how violence and revenge are represented through the storyline, characterization, and cinematic symbolism, while also examining the ethical dimensions debated in public and academic discourse. The research method used is a qualitative study based on a literature review with an interdisciplinary approach, namely literary narrative theory, the ethics of violence representation, and cultural political analysis. Data was obtained from academic journals, film reviews, and literature related to the representation of violence in cinema. The results of the study show that Spielberg refuses to give absolute legitimacy to state violence or individual revenge, but rather opens up a space of moral ambiguity that challenges the audience to reflect. The narrative of revenge in Munich is depicted as an endless cycle that traps perpetrators, victims, and nations in repeated trauma. Finally, Munich serves as a reminder that revenge, no matter how strong the political or emotional motivations behind it, is never free from ethical consequences.